The role of corporate social responsibility in management of sustain able business : a case study of the telecom industry in Uganda (2004 -2011) - Kabagyenyi, Susan H. (Kampala, 2012)
Unpublished dissertation (MA. LHRS) - Makerere University, 2012.
Includes bibliographical references.
Keywords: Social responsibility of business; Corporate governance -- Uganda; Sustainable development -- Uganda